Keyword-aware optimal route planning method for large-scale graph data - Ziyang LI; Pengcheng CHEN; Jiong YU; Yonglin PU; Zhenzhen HE; Xue LI; Shijie ZHENG (Tongxin xuebao, 2023)
Focused on the problem that the planned routes cannot meet the personalized demand of different users in route planning of personalized self-driving tour, a keyword-aware optimal route planning method based on different user interests was proposed.Firstly, the road network information preprocessing model was set up and the road network information query graph was built by the road network information preprocessing algorithm.Secondly, the inverted index algorithm was proposed to prune the road network information query graph according to the personalized requirements from users, which improved the execution efficiency of keyword-aware optimal route planning method and reduced the memory cost of large-scale data processing effectively.Finally, the keyword-aware optimal route planning algorithm was proposed to realize personalized recommendation according to user interest by bidirectional parallel extension.The experimental results show that the method not only realizes the route planning to meet the individual needs of users but also improves the execution efficiency of the method through pruning and bidirectional parallel extension.